Surgical consent during the COVID-19 pandemic. (November 2020) - Rotimi, O.; Beatson, K.; Aderombi, A.; Lam, W.; Bajomo, O.; Kukreja, N.
Abstract: Background and aims: During the COVID-19 pandemic, surgical practice may deviate with operative and non-operative management considered. Appropriate discussion of options with patients is paramount to quality surgical care. Intercollegiate and EAES guidelines recommend discussing and documenting risk of COVID-19 exposure in the consent process for patients undergoing surgery. Materials and methods: Closed-loop audit of consent forms for patients undergoing emergency and elective surgical procedures. Interventions implemented included education of wider surgical teams. Data was collected during a one-week period for each cycle and analysed using Chi-squared test. Results: In cycle 1, 6/17 (35.3%) case notes documented discussion of COVID-19 risk. Following intervention, compliance improved to 23/29 (79.3%) cases in cycle 2 and 33/45 (73.3%) cases in cycle 3. Conclusion: Pre-intervention, our consenting practice was non-compliant. Our interventions led to significant and sustained improvements in practice. We recommend provision of wider surgical team education to facilitate good consenting practice. Highlights: Surgical consent practice has changed as a result of COVID-19. Patients should be consented for COVID-19 as this risk is now pertinent to all patients listed for surgery. Simple interventions can be extremely effective in improving long-term consenting practice.